A facile synthesis approach of Li2MnO3 cathode material for lithium-ion battery by one-step high-energy mechanical activation method. (23rd August 2020) - Hu, Guorong; Xue, Zhichen; Wang, Weigang; Zhu, Fangjun; Sun, Qian; Huang, Jiangnan; Peng, Zhongdong; Cao, Yanbing; Du, Ke
ABSTRACT: In this article, Li2 MnO3 was successfully prepared by a facile one-step high-energy mechanical activation method free from sintering. XRD, SEM, and TEM techniques were employed to analyse the materials, meanwhile the electrochemical properties of the obtained material are studied. XRD result shows that the desired material Li2 MnO3 can be obtained just by high-energy ball milling without sintering, and the existence of Li2 MnO3 was further proved by XPS. The obtained materials by high-energy ball milling are in a nano-scale range from 20 to 100 nm, which was confirmed by TEM and SEM. The electrochemical tests show that the prepared materials can be directly put into use as the cathode of lithium-ion batteries without secondary treatment. Successful preparation of Li2 MnO3 by high-energy mechanical activation method provides a breakthrough for the low energy consumption and environmentally friendly industrialisation of new powder materials.